Uji Pengaruh Faktor Kependudukan terhadap Keberadaan Pelayanan Jasa Ekspedisi di Desa / Kelurahan Kabupaten Bandung Barat - Fatia Amalia Maresti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
West Bandung Regency is a new district in West Java with a lot of potential, including a strategic geographical position on the West Java and DKI Jakarta crossing routes, natural resources and potential energy that provide added value, and adequate tourism resources. The existence of expedition service providers has a strategic role in improving the performance of the flow of goods to an area. Factors that significantly influence the existence of expedition services in the villages of West Bandung Regency in 2019 and 2020 based on the results of the t-student test are the number of private employees (p-val 0.005), the number of population aged 15-39 years (p-val 0.021), number of entrepreneurs (p-val 0.032), and number of micro and small industries (p-val 0.037). Other significant factors of the categorical variable based on the chi-squared test are District Location (p-val < 2.2 .10-16) and Main Source of Income (p-val 8.1 .10-16).